The Resemblances between Silvia Plath's Life and Her "The Bell Jar" - Kurnianto, Ery Agus (SIGEH ELT : Journal of Literature and Linguistics, 2024)
AbstractThe Bell Jar is a novel written by Sylvia Plath. It is searing semi autobiographical with mental illness character described by Esther which is believed to be the resemblance of Plath’s life. In this study, there are aspects which drew the writers’ attention through the mirrored lives of two women, the fictional one Esther Greenwood and Plath as the author of The Bell Jar. Specifically, the writers focus on women’s writing and woman’s psyche in gaining the answer about the narrative life of Sylvia Plath through Esther character. This study used library study to find any related data and descriptive qualitative method in the analysis. At the end, the study reveals that The Bell Jar novel reflects the the life of Plath through Esther character. Those are life as a writer, about her love relation and family relation.